2015
DOI: 10.3168/jds.2014-8764
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of milk mid-infrared spectra from a European dairy network

Abstract: The goal of this study was to find a procedure to standardize dairy milk mid-infrared spectra from different Fourier transform mid-infrared spectrophotometers (different brands or models) inside a European dairy network to create new farm-management indicators (e.g., fertility, health, feed, environmental impact) based on milk infrared spectra. This step is necessary to create common spectral databases, allowing the building of statistical tools, to be used by all instruments of the network. The method used wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
116
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(122 citation statements)
references
References 17 publications
6
116
0
Order By: Relevance
“…A previous study (Grelet et al, 2015) demonstrated that until now it was possible to transfer only high-quality models (fat). The results confirm the first conclusions obtained with the fat model: without the use of a standardization step, the transfer of models leads to considerable errors in the predictions, reducing the value of information from FT-MIR milk spectra for Figure 4.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A previous study (Grelet et al, 2015) demonstrated that until now it was possible to transfer only high-quality models (fat). The results confirm the first conclusions obtained with the fat model: without the use of a standardization step, the transfer of models leads to considerable errors in the predictions, reducing the value of information from FT-MIR milk spectra for Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…Plots representing the link between the quality of the model (coefficient of determination of cross-validation; R 2 cv) and the performance of the transfer by piecewise direct standardization [relative root mean squared error (RMSE) between slaves and master predictions after standardization] from the 5 interlaboratory study samples analyzed on 66 instruments. CH 4 = methane emitted by dairy cows; PUFA = PUFA in milk; FCY = fresh cheese yield; Fat = fat model used in Grelet et al (2015). reproducibility of wave number areas selected within the models.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations